2013
DOI: 10.1002/jez.1833
|View full text |Cite|
|
Sign up to set email alerts
|

Do cortisol and corticosterone play the same role in coping with stressors? Measuring glucocorticoid serum in free‐ranging guanacos (Lama guanicoe)

Abstract: Habitat can constrain and shape successful ecological and physiological strategies, thus providing the context for the evolution of life-history traits. However, unpredictable challenges, such as storms, natural disasters, and human activities can also have great effects on stress. Glucocorticoids (GCs) are adrenal steroid hormones that play an important role in how vertebrates cope with these predictable and unpredictable environmental challenges. Although assessing GCs levels can have many applications in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(80 reference statements)
2
4
0
Order By: Relevance
“…The physiological stress response was demonstrated by an initial increase in both catecholamines and rectal temperature, which were greater after longer chases, followed by a prolonged increase in corticoids, which continued to increase during handling. Our results are broadly consistent with previous findings in Svalbard reindeer 14 and other ungulates, including free-ranging impala (Aepyceros melampus) 16 , guanacos (Lama guanacoe) 38 , and vicuña (Vicugna vicugna) 39 , although the specific responses to being chased and restrained may vary between species. For instance, in guanacos, cortisol increased with handling time, but corticosterone did not 38 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The physiological stress response was demonstrated by an initial increase in both catecholamines and rectal temperature, which were greater after longer chases, followed by a prolonged increase in corticoids, which continued to increase during handling. Our results are broadly consistent with previous findings in Svalbard reindeer 14 and other ungulates, including free-ranging impala (Aepyceros melampus) 16 , guanacos (Lama guanacoe) 38 , and vicuña (Vicugna vicugna) 39 , although the specific responses to being chased and restrained may vary between species. For instance, in guanacos, cortisol increased with handling time, but corticosterone did not 38 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results are broadly consistent with previous findings in Svalbard reindeer 14 and other ungulates, including free-ranging impala (Aepyceros melampus) 16 , guanacos (Lama guanacoe) 38 , and vicuña (Vicugna vicugna) 39 , although the specific responses to being chased and restrained may vary between species. For instance, in guanacos, cortisol increased with handling time, but corticosterone did not 38 . In contrast, both cortisol and corticosterone increased during handling in our study.…”
Section: Discussionsupporting
confidence: 91%
“…However, whereas corticosterone is a more adaptation-related biomarker than cortisol during chronic stress, cortisol is a quicker responder than corticosterone during severe acute stress. In guanacos (Lama guanicoe), it has been shown that cortisol and corticosterone exhibit different patterns in the field and in response to acute stressors [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that corticosterone is the main glucocorticoid in plasma, prevalence of cortisol over corticosterone was revealed in some organs such as kidneys, spleen, heart and brain [ 19 ]. Furthermore, in wild species, both cortisol and corticosterone are formed in a species-specific extent and may vary in ratio according to the demands [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a switch from corticosterone dominance to cortisol dominance in response to chronic stress has been observed in rabbits (Kass et al ., 1954), serum GCs exhibited different patterns in response to acute stressors in llamas ( Lama guanicoe ; Ovejero et al ., 2013), and in rodents ( Ctenomys talarum ) the plasma cortisol increased after an ACTH challenge but corticosterone did not, even though corticosterone levels were higher than cortisol levels (Vera et al ., 2012). Furthermore, rodents also had significant inter-annual variation in the levels of corticosterone, which resulted in a pronounced change in the cortisol: corticosterone ratio in plasma.…”
Section: Discussionmentioning
confidence: 99%